Food Stall in Ruteng: A Linguistics Landscape Study - Jem, Yosefina; Jemadi, Fransiskus; Beda, Raymundus; Khasanah, Nurul; Rafael, Agnes M.D (Jurnal Pendidikan dan Kebudayaan Missio, 2026)
This study examines the linguistic landscape (LL) of food stall signage in Ruteng by analyzing the linguistic forms, typologies, and communicative functions embedded within bottom-up commercial signs. Grounded in LL theory and enriched by geosemiotic, mobility, and language ideology perspectives, the research employed a descriptive qualitative design to explore how language operates symbolically and informationally in everyday public spaces. Thirty-six food stall signs were collected through field observation and analyzed for their linguistic composition, spatial emplacement, and semiotic features. The findings reveal that Indonesian overwhelmingly dominates monolingual signage, reflecting national language policy and shared linguistic norms, while bilingual and multilingual signs incorporate regional languages, Arabic, and English to index ethnic identity, religious affiliation, cultural heritage, or aspirations toward modernity. All signs constitute bottom-up signage, highlighting individual agency and cultural creativity in shaping the local LL. Functionally, the signs perform both informational roles—such as conveying menu offerings and halal status—and symbolic roles, expressing identity markers, migration histories, and ideological values. Overall, the study demonstrates that food stall signage in Ruteng functions as a meaningful semiotic artifact that materializes the intersection of language, identity, and mobility in the public sphere, offering valuable insights into the sociolinguistic dynamics of multilingual Indonesian communities.